2017
DOI: 10.1088/1475-7516/2017/08/024
|View full text |Cite
|
Sign up to set email alerts
|

Black holes in vector-tensor theories

Abstract: We study static and spherically symmetric black hole (BH) solutions in second-order generalized Proca theories with nonminimal vector field derivative couplings to the Ricci scalar, the Einstein tensor, and the double dual Riemann tensor. We find concrete Lagrangians which give rise to exact BH solutions by imposing two conditions of the two identical metric components and the constant norm of the vector field. These exact solutions are described by either Reissner-Nordström (RN), stealth Schwarzschild, or ext… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
105
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 128 publications
1
105
0
Order By: Relevance
“…To proceed we assume that h(r) = f (r). Making use of the field equations calculated in [29] (translating from a vectortensor theory to a shift-symmetric scalar-tensor theory such that A µ → ∂ µ φ , i.e. A 0 = X 0 = 0, A 1 = dφ /dr), we find the following hairy solution:…”
Section: Cubic Termmentioning
confidence: 99%
See 3 more Smart Citations
“…To proceed we assume that h(r) = f (r). Making use of the field equations calculated in [29] (translating from a vectortensor theory to a shift-symmetric scalar-tensor theory such that A µ → ∂ µ φ , i.e. A 0 = X 0 = 0, A 1 = dφ /dr), we find the following hairy solution:…”
Section: Cubic Termmentioning
confidence: 99%
“…It can be easily shown that spherically symmetric BHs can indeed have hair. For instance, [29] shows the solution when G 3 = 0, G 4 = M 2 P /2, in which case:…”
Section: Generalised Procamentioning
confidence: 99%
See 2 more Smart Citations
“…Focusing, for obvious reasons, on the coupled case, we adopt a largely theory-agnostic approach and postulate a pair of wave equations for the tensorial and the extra 'scalar' field with parametrised potentials. Although far from representing the most general situation [23], our parametrised model provides a useful benchmark for describing perturbed non-GR black holes; in addition it has the merit of including as a special case at least a pair of modified theories of gravity, namely, dynamical Chern-Simons gravity [16] and the sixth-order Proca theory [23,25].…”
Section: Introductionmentioning
confidence: 99%